(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research :Perhaps the success of the educational process depends greatly on the nature of the interaction between the teacher and the learners on the one hand, and between the learners among themselves on the other hand, according to the nature of the course or topics that require interaction as a stimulus for achievement, whether that is due to planning for education or teaching by the teacher in an organized and planned manner in advance. Thus, it pushes the education process from the level of indoctrination to the level of participation and integration with work, and the actions, words or opinions, dialogues and movements that take place within the classroom space and which are organized by the teacher may be with the aim of achieving better learning or developing the learner’s true desire to learn, and it is taken Several forms, including verbal and non-verbal, such as signs, gestures, and movements, aim to communicate and achieve attention to educational situations with continuous activity. Both Rocky and BarryRoky emphasized that the methods of treatment on the part of the teacher, which are flexible and democratic, lead to an increase in the learner’s ability to think creatively. Ahern also studied a sample of (144) learners and (35) teachers and concluded that there is a positive relationship between the ability to think creatively among learners in education spaces centered on the interaction between the teacher and the learner. Many learning theories and teaching strategies emphasized the importance of classroom interaction, communication, and intimacy, as they are considered a fundamental basis for effective and active learning. Today we are facing a situation or practice that is almost new in terms of the necessity of application in the educational process and what resulted from the global crisis of the Corona pandemic, which imposed that virtual education be an alternative, an option, or a method to complete the progress of the educational process, and the accompanying some obstacles that we will highlight an important part. Including in the virtual educational space from an educational point of view to the extent of the impact on the communication process between the teacher and the learner. The educational process may be affected by human and social communicative and interactive processes, which in their entirety affect the educational practice. The interaction of the teacher with the learners is of great importance in the learning process, determined by the nature of the educational situation and what is related to it and its contribution to building interests, trends and inclinations, and what is reflected in the learner’s performance in academic achievement and the development of team spirit. Generating a sense of belonging and establishing relationships in which an atmosphere of familiarity and understanding prevails, and thus interaction can be considered an important pillar in the educational process. Class interaction processes are also one of the prevailing trends in teacher performance evaluation until it has become a scientific subject for experimental researchers in the field of learning by taking an observational approach in studying teacher behavior within the classroom and monitoring interactions that occur in educational situations.In this analytical study, the researcher relied on several axes:1. Characteristics of class interaction.2. The role of the teacher and the learner in classroom interaction.3. The systems that dealt with classroom interaction measurement.Keywords: virtual presence, virtual presence, blended learning.